What Is the Treatment "Algorithm" for Infection After Achilles Tendon Repair/Reconstruction?. (July 2019) - Winters, Brian; Da Rin de Lorenzo, Ferdinando; Beck, David
Recommendation: The initial treatment of an infected Achilles tendon reconstruction should include thorough debridement of all infected tissues with the removal of retained sutures or foreign material. Cultures should be taken at the time of debridement, and antibiotic administration should be dictated by the result of culture and continued until inflammatory markers and clinical symptoms normalize. If significant soft tissue defect in the overlying area remains, the choice of tendon reconstruction and/or transfer with soft tissue coverage should be left up to the discretion of the treating surgeon based on preference and expertise. Revision reconstruction should be delayed until the infection is cleared. Level of Evidence: Moderate. Delegate Vote: Agree: 100%, Disagree: 0%, Abstain: 0% (Unanimous, Strongest Consensus).